CONTEÃšDO EM CÃLCIO, PROTEINA E VITAMINA C EM DOZE VARIEDADES DE COUVE (ð˜‰ð˜³ð˜¢ð˜´ð˜´ð˜ªð˜¤ð˜¢ ð˜°ð˜ð˜¦ð˜³ð˜¢ð˜¤ð˜¦ð˜¢) - Crocomo, Otto J.; Salibe, Ary A. (REVISTA DE AGRICULTURA, 2020)
CONTEÃšDO EM CÃLCIO, PROTEINA E VITAMINA C EM DOZE VARIEDADES DE COUVE (ð˜‰ð˜³ð˜¢ð˜´ð˜´ð˜ªð˜¤ð˜¢ ð˜°ð˜ð˜¦ð˜³ð˜¢ð˜¤ð˜¦ð˜¢)